2022
DOI: 10.3390/jcm11154256
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Failed Trial of Labor after Cesarean, among Women with Twin Gestation—A Multicenter Retrospective Cohort Study

Abstract: Objective: Twin trial of labor after a cesarean section (TOLAC) is associated with a lower success rate of vaginal delivery than singleton TOLAC, and a higher rate of adverse outcomes in comparison to an elective repeat cesarean delivery. This study aims to investigate the factors associated with failed TOLAC, among women with twin gestation. Study design: A multicenter retrospective cohort study was undertaken. All women with twin pregnancies attempting a trial of labor after a previous cesarean in two univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The authors concluded that compared to the remifentanil-PCA control, the use of EA decreases the incidence of CS for the delivery of both fetuses in twin gestation, as well as the frequency of combined CS and vaginal delivery for the birth of the second twin. Similarly, it was recently shown that in parturients with twin gestation attempting a trial of labor after a previous CS, using EA may decrease the risk of a repeat CS [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that compared to the remifentanil-PCA control, the use of EA decreases the incidence of CS for the delivery of both fetuses in twin gestation, as well as the frequency of combined CS and vaginal delivery for the birth of the second twin. Similarly, it was recently shown that in parturients with twin gestation attempting a trial of labor after a previous CS, using EA may decrease the risk of a repeat CS [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ford et al showed an increase (0.9%) scar rupture compared with the lower value in singleton with one previous lower segment scar [51,55]. In a recent multicenter retrospective cohort study with a sample size of 160 women with twin A in vertex position with a single previous lower segment caesarean section, Peled et al [56] stated that successful VBAC in selected twin was achieved in 86.3% while Levin et al [41] reported a success VBAC rate of 31.3% in women with twins who attempted VBAC with no prior vaginal delivery.…”
Section: Twin Gestationmentioning
confidence: 98%
“…TOLAC, on the other hand, is known to raise the chance of uterine rupture. According to expert opinion, TOLAC is the best treatment for women who do not have multiple risk factors [22]. However, the patient should be informed about the availability of an obstetrician and anesthetist on-site.…”
Section: The Outcomes Among Women Who Underwent Trial Of Labor After ...mentioning
confidence: 99%